Evaluation of Renal Functional Status Using Probe Renogram Technique and USG - Ahasan, MM; Ahmed, Fariduddin; Shah, Kabir uz Zaman; Khanama, MN; Badrudozza, SM (TAJ: Journal of Teachers Association, 2009)
Renal disorder is one of the most common problems in Bangladesh. Probe renogram is a very sensitive, specific, non-invasive and cost-effective procedure for the evaluation of renal function. Ultrasonography gives good anatomical information. It is cheap, non-time consuming and non-invasive procedure that requires no extra-preparation for studying kidneys. Combined renogram and USG were found to be very useful techniques for the evaluation of kidney's functions. Biochemical parameters do not reflect the appropriate functional status of individual kidneys. Probe-renogram could reveal precisely the renal differential function. Retrospectively 129 patients were studied, of which 80 (62.02%) were male and 49 (37.98%) were female, age between 8-78 years had come at the NMC, Rajshahi during the period of April 2000 to July 2001 for radionuclide renography. The main objective of the study was to evaluate the response of combined renogram and USG for preliminary screening of renal disorders in patients before going to other high cost and invasive investigations. Renal obstructions were found in 42 (LK-2G and RK-16) cases and functional impairment of varying degrees was in 55 patients. Results were correlated well with clinical findings and other available diagnostic parameters. doi: 10.3329/taj.v15i2.3907 TAJ December 2002; Vol.15(2):56-58